ASSOCIATION BETWEEN PSYCHOLOGICAL DISTRESS, SLEEP QUALITY, AND VARIABILITY OF PHYSIOLOGICAL VAGINAL DISCHARGE AMONG ADOLESCENT GIRLS - Regina Ayu Fristiyanti; Suci Fitriana Pramudya Wardani; Irna Olvaliani Aimang; Nur Sophia Matin (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
Physiological vaginal discharge is a normal condition in adolescent girls, yet variations in its characteristics often cause concern. Psychological distress and sleep quality are suspected to influence the variability of physiological vaginal discharge. This study aimed to analyze the relationship between psychological distress, sleep quality, and the variability of physiological vaginal discharge in adolescent girls. This cross-sectional study involved 120 female students aged 15–18 years at a Banyuwangi Regency high school. Psychological distress was measured using the Kessler Psychological Distress Scale (K10), sleep quality using the Pittsburgh Sleep Quality Index (PSQI), and discharge variability was categorized into